Religious dietary rules and their potential nutritional and health consequences. (18th November 2020) - Chouraqui, Jean-Pierre; Turck, Dominique; Briend, André; Darmaun, Dominique; Bocquet, Alain; Feillet, François; Frelut, Marie-Laure; Girardet, Jean-Philippe; Guimber, Dominique; Hankard, Regis; Lapillonne, Alexandre; Peretti, Noel; et al.
Abstract: Background: The vast majority of the world population declares affiliation to a religion, predominantly Christianity and Islam. Many religions have special dietary rules, which may be more or less strictly adhered to. Methods: Religious food rules were collected from holy books and religious websites as well as their translation into dietary practices. The literature was searched for potential associations between these rules and potential nutritional consequences. Results: Jewish, Islamic and Indian religions support prolonged breastfeeding. Religious avoidance of alcohol is probably beneficial to health. When strictly applied, a few rules may lead to nutritional inadequacies, mainly in populations living in unfavourable socio-economic or environmental conditions. In Jewish and Muslim observants, animal slaughtering procedures may increase the risk of iron deficiency. Jews may be at risk of excess sodium intake related to home-prepared foods. A vegan diet, as observed by some believers, often by drifting from original precepts, or by some Hindus or Buddhists, may result in vitamin B12, calcium, iron, zinc, selenium and n -3 fatty acids deficiencies. Conclusion: When implemented in accordance with the rules, most religious food precepts are not detrimental to health, as suggested by the fact that they have more or less been followed for millennia. Nevertheless, some practices may lead to nutritional inadequacies, such as iron, calcium, vitamin D and vitamin B12 deficiencies. Patients with low socio-economic status, children and women of childbearing age are of particular risk of such deficiencies. Being aware of them should help health professionals to take an individualized approach to decide whether to supplement or not.